Tuntutan Hak Nafkah Istri yang tidak di Biayai oleh Suami Selama Dua Tahun Menurut Kompilasi Hukum Islam (KHI) - Hadiwidjaja, Moch Eryans; Yani, Encep Ahmad (Wajah Hukum, 2025)
This study examines the wife's claim for maintenance rights that has not been met by the husband for two years based on Article 80 paragraph (4) of the Compilation of Islamic Law (KHI), which requires the husband to provide for his wife and children according to his ability. Using a normative approach with statute and conceptual methods, this study analyzes legal regulations such as Law Number 1 of 1974 concerning Marriage, the 1945 Constitution, and the Bandung Religious Court's decision Number 6147/Pdt.G/2024/PA.Badg as a case study. The results show that a husband's negligence in providing maintenance can be grounds for divorce, supported by Gustav Radbruch's basic legal values of justice, certainty, and expediency. The wife has the right to file a claim through mediation or litigation in the Religious Court to obtain protection of her rights, in order to create a harmonious family and social welfare. This study emphasizes the importance of law enforcement to protect women in marriage.